S-band Q-switched fiber laser using molybdenum disulfide (MoS2) saturable absorber - Ahmad, Harith; Ismail, Mohd Afiq; Suthaskumar, Muneswaran; Cheak Tiu, Zian; Harun, Sulaiman Wadi; Zulkifli, Mohd Zamani; Samikannu, Sathiyan; Sivaraj, Sivabalan (IOP Publishing, 2016)
In this letter, a molybdenum disulfide (MoS2) saturable absorber (SA) is fabricated using a simple drop cast method to generate Q-switched fiber laser operating in the S-band region (1460 nm–1530 nm). The MoS2 solution was prepared using the liquid phase exfoliation (LPE) method where MoS2 crystals were added into dimethylformamide (DMF) solvent and subsequently sonicated and centrifuged. They were then repeatedly dripped onto fiber ferrules and dried in an oven. The resultant Q-switched fiber laser starts with some physical disturbance when the pump power was set at 40 mW and continues to operate until the pump power reaches 120 mW. The resultant repetition rate varies with pump power between 27.17 to 101.17 kHz while the changes in pulse widths are from 3.0 to 1.4 μs.